On the application of numerical methods to the solution of nonlinear second-order differential equations with random deviations of argument - Kolomiets, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider the application of the Krylov-Bogolyubov-Mitropol’skii asymptotic method and Runge-Kutta methods to the investigation of oscillating solutions of quasilinear second-order differential equations with random deviations of argument. For specific equations, we obtain approximate numerical solutions and characteristics of random oscillations.